Peningkatan Pendapatan Petani Melalui Edukasi Pemanfaatan Pestisida Nabati Ramah di Lingkungan Berbasis Bahan Lokal - Jeki Algusri; Ananda Rahmadhani; Aulia Sabilla Salim; Khalilah Galih Farahdita; Muhammad Grezka Harviano; Mhd Wafiq Ramadhan; Nurmaini Nurmaini; Olipian Resky Pernando; Raihan Akbar; Winda Sugiarti; Indra Pratama; Nanda Safira; Niswatun Fitriyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to increase the income of farmers in Delima Jaya Village through education on the use of lemongrass-based botanical pesticides as an alternative to chemical pesticides. The main problems faced by farmers are high production costs and the health and environmental risks associated with the use of synthetic pesticides. The activity was carried out using a participatory method through surveys, outreach, training on botanical pesticide production, field mentoring, and program impact evaluation. The results showed that farmers were able to produce botanical pesticides independently at 80% lower costs than chemical pesticides. Field trials demonstrated the effectiveness of botanical pesticides in controlling pests, increasing crop yields by 10–15%, and increasing farmer incomes by up to IDR 3.5–3.8 million per planting season. The program also raised farmers' awareness of the importance of sustainable agricultural practices utilizing local resources. Overall, education on the use of lemongrass-based botanical pesticides has proven effective in reducing production costs, increasing farmer productivity and welfare, and supporting environmental sustainability. This local potential-based empowerment model can be replicated in other villages to create an environmentally friendly and competitive agricultural system. Additionally, the program fostered greater awareness among the farmers regarding the importance of sustainable agricultural practices, such as reducing the use of synthetic chemicals and leveraging locally available plants for pest control. This empowerment model, based on local potential, can be replicated in other villages to promote an environmentally friendly and economically viable agricultural system.